Determinants of arterial stiffness in chronic kidney disease stage 3 - McIntyre, Natasha J.; Fluck, Richard J.; McIntyre, Christopher W.; Fakis, Apostolos; Taal, Maarten W. (Public Library of Science, 2013)
Background: Early chronic kidney disease (CKD) is associated with increased cardiovascular (CV) risk but underlying mechanisms remain uncertain. Arterial stiffness (AS) is associated with increased CV risk in advanced CKD, but it is unclear whether AS is relevant to CV disease (CVD) in early CKD. Study Design: Cross-sectional. Setting and participants: 1717 patients with previous estimated glomerular filtration rate (eGFR) 59–30 mL/min/1.73 m2; mean age 7369y, were recruited from 32 general practices in primary care. Outcomes: Increased arterial stiffness. Measurements: Medical history was obtained and participants underwent clinical assessment, urine and serum biochemistry testing. Carotid to femoral pulse wave velocity (PWV) was determined as a measure of AS, using a VicorderTM device. Results: Univariate analysis revealed significant correlations between PWV and risk factors for CVD including age (r = 0.456; p,0.001), mean arterial pressure (MAP) (r = 0.228; p,0.001), body mass index (r = 20.122; p,0.001), log urinary albumin to creatinine ratio (r = 0.124; p,0.001), Waist to Hip ratio (r = 0.124, p,0.001), eGFR (r = 20.074; p = 0.002), log high sensitivity c-reactive protein (r = 0.066; p = 0.006), HDL (r = 20.062; p = 0.01) and total cholesterol (r = 20.057; p = 0.02). PWV was higher in males (9.6 m/sec vs.10.3 m/sec; p,0.001), diabetics (9.8 m/sec vs. 10.3 m/sec; p,0.001), and those with previous CV events (CVE) (9.8 m/s vs. 10.3 m/sec; p,0.001). Multivariable analysis identified age, MAP and diabetes as strongest independent determinants of higher PWV (adjusted R2 = 0.29). An interactive term indicated that PWV increased to a greater extent with age in males versus females. Albuminuria was a weaker determinant of PWV and eGFR did not enter the model. Limitations: Data derived from one study visit, with absence of normal controls. Conclusion: In this cohort, age and traditional CV risk factors were the strongest determinants of AS. Albuminuria was a relatively weak determinant of AS and eGFR was not an independent determinant. Long-term follow-up will investigate AS as an independent risk factor for CVE in this cohort.